A clean and industrially applicable approach for the production of copper-doped and core-shell structured porous carbon microspheres as supercapacitor electrode materials. (1st February 2021) - Chen, Weimin; Luo, Min; Yang, Kai; Zhang, Daotong; Zhou, Xiaoyan
Abstract: Conventional approaches for the production of copper-doped porous carbon microspheres from biomass involve a multi-step process, including spherical-shape development, carbonization, activation, and thermal treatment in the presence of a copper donor. In this work, a clean and industrially suitable approach is proposed to directly prepare copper-doped porous carbon microspheres from enzymatic hydrolysis lignin by utilizing cupric chloride dihydrate in four aspects: (1) as a microwave absorber to rapidly elevate the heating temperature, achieving an exceedingly short production duration of 8 min and a high carbon yield of 35.1%, (2) as a sphering agent to build a core-shell structure containing disordered carbon in the shell layer and copper-related particles in the core layer, limiting the volume changes of the copper-related particles and restraining their aggregation, (3) as a porogen to obtain a hierarchical porous structure with a high specific surface area of 1083 m 2  g −1 and a mesopore ratio of 44.2%, and (4) as a copper donor to grow abundant copper-related particles, bypassing the purification process. The porous structure ensures the rapid ion transport for the copper-related particles which in turn provide a significant pseudo-capacitance. The resultant electrode achieves a remarkably high specific capacitance of 736 F g −1  at 1 A g −1 . Moreover, the fabricated supercapacitor delivers an energy density of up to 43.9 W h kg −1  at 0.5 kW kg −1 . This work demonstrates a clean and industrially applicable method to utilize biomass waste in high-value-added electrode materials with a low overall production cost. Graphical abstract: Image 1 Highlights: A very short production duration of 8 min and a high yield of 35.1% are achieved. CuCl2 acts as a microwave absorber, sphering agent, porogen, and Cu donor. A novel core-shell and Cu-doped structure is constructed. A remarkably high energy density of 43.9 W h kg −1 is achieved at 0.5 kW kg −1 .